1995
DOI: 10.1172/jci117757
|View full text |Cite
|
Sign up to set email alerts
|

A functional role for endogenous atrial natriuretic peptide in a canine model of early left ventricular dysfunction.

Abstract: Asymptomatic or early left ventricular dysfunction in humans is characterized by increases in circulating atrial natriuretic peptide (ANP) without activation of the renin-angiotensin-aldosterone system (RAAS). We previously reported a canine model of early left ventricular dysfunction (ELVD) produced by rapid ventricular pacing and characterized by an identical neurohumoral profile and maintenance of the natriuretic response to volume expansion (VE). To test the hypothesis that elevated endogenous ANP suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
59
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(63 citation statements)
references
References 37 publications
3
59
0
1
Order By: Relevance
“…These findings were surprising in view of improved CO in the PDE VI-treated group. Previous studies demonstrated a compensatory role for the endogenous NP to maintain renal hemodynamic and excretory function in CHF (20). In the PDE VI group, however, there was a strong trend for plasma BNP to be lower as compared with the untreated CHF group.…”
Section: Discussionmentioning
confidence: 70%
“…These findings were surprising in view of improved CO in the PDE VI-treated group. Previous studies demonstrated a compensatory role for the endogenous NP to maintain renal hemodynamic and excretory function in CHF (20). In the PDE VI group, however, there was a strong trend for plasma BNP to be lower as compared with the untreated CHF group.…”
Section: Discussionmentioning
confidence: 70%
“…Newfoundlands, on the other hand, had low renin activity and high ET‐1 as well as NT‐proBNP concentration 11. Natriuretic peptides are known to suppress RAAS activation in dogs as well as people,32, 33 and ET‐1 has been suggested to inhibit renin production, but the interaction between hormonal systems is complex 34. Taken together, the present results indicate that if ET‐1 and natriuretic peptides are high, the renin activity is low and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model of early left ventricular dysfunction without overt heart failure, plasma norepinephrine levels are elevated, indicative of early SNS activation (2). Power spectral analysis of heart rate variability suggests that there is sympathetic activation early in the course of left ventricular dysfunction in a canine model of heart failure (3).…”
Section: Introductionmentioning
confidence: 99%